Efficacy of low doses of (E, Z)-2,4-ethyl decadienoate and synthetic pheromone blends to monitor Cydia pomonella (Lepidoptera Tortricidae) adults (Bollettino di zoologia agraria e bachicoltura, 2024)
Trials were carried out to assess the possible attractive effect of the pear ester (E, Z)-2,4-ethyl decadienoate (DA2313) and the synthetic pheromone (E,E)-8,10-dodecadienol on the behaviour of Cydia pomonella adults. Field trials were conducted in five different sites, four in Italy and one in France. Traps baited with the pear ester alone, with the synthetic pheromone alone, and with different blends of the two compounds were placed in the field. Trap catches were recorded weekly. The synthetic pheromone caught more males than the pear ester, while the latter alone was the most attractive to females. Blends of pear ester and pheromone at different doses were not as effective as the pear ester alone to capture females.
Keywords: plant volatiles; sex pheromone; codling moth; monitoring; field test